2005
DOI: 10.1016/j.snb.2004.05.033
|View full text |Cite|
|
Sign up to set email alerts
|

Monitoring the exhaust air of a compost pile as a process variable with an e-nose

Abstract: In this paper, the monitoring of the composting process with an e-nose is presented. An emission chamber is developed for this purpose and put on a household waste compost pile. A lab-made e-nose with metal oxide sensors is located at the exit of this chamber. Simultaneously to the e-nose measurements, air sampling on sorbent tubes as well as physico-chemical analysis are realised. The adsorbed air samples are analysed in the lab by gas chromatography coupled to mass spectrometry (GC-MS). In addition, some par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…1) was adapted from the systems described in [22][23][24]. Sensors were selected according to the biogas composition.…”
Section: Monitoring With the E-nosementioning
confidence: 99%
“…1) was adapted from the systems described in [22][23][24]. Sensors were selected according to the biogas composition.…”
Section: Monitoring With the E-nosementioning
confidence: 99%
“…Moreover, the composition of the compost exhaust air indicates the aeration status of the process and the quality of the final product (4,5). Previous research identified the probable biomarker gases released by swine mortalities inside biosecure compost systems (6)(7)(8) as dimethyl disulfide (DMDS), dimethyl trisulfide (DMTS), and pyrimidine.…”
Section: Introductionmentioning
confidence: 99%
“…Nicolas et al [9] used PCA to evaluate data from an electronic nose. The correlations between the sensor of an electronic nose and chemical substances were determined by Romain et al [11] using PCA. PCA was applied to observations of a composting process by means of analytical electrofocusing.…”
Section: Pattern Recognition Calibrationmentioning
confidence: 99%